Management of inflammatory bowel disease and serum level of infliximab in newborn exposed to anti-TNF therapy during pregnancy: Case report and literature review - De Aragão, Maria Cecília [UNESP]; Beraldo, Rodrigo Fedatto [UNESP]; Marcondes, Mariana Barros [UNESP]; De Barros, Jaqueline Ribeiro [UNESP]; Herrerias, Giédre Soares Prates [UNESP]; Saad-Hossne, Rogerio [UNESP]; Baima, Júlio Pinheiro [UNESP]; Sassaki, Ligia Yukie [UNESP] (Wolters Kluwer, 2021)
Rationale:Heightened inflammatory bowel disease (IBD) activity during pregnancy is associated with higher rates of preterm birth, miscarriage, and low birth weight. Therefore, its adequate treatment is essential, considering the risk-benefit of medication use. Although previous literature has described the management of IBD during pregnancy, few studies have assessed the pharmacokinetics of IBD drugs in the newborn. In this case report, we describe the management of ulcerative colitis during pregnancy and discuss the benefits of checking serum levels of infliximab in newborns exposed to the medication during pregnancy.Patient concern:A 37-year-old patient with ulcerative colitis in clinical and endoscopic remission had been undergoing treated with infliximab since 2008. The patient became pregnant in 2018.Diagnosis and intervention:Infliximab medication was discontinued at the 29th week of pregnancy.Outcomes:The pregnancy was uneventful, and the levels of infliximab in the umbilical cord were >20μg/dL. Live vaccinations were postponed until the baby was 6months old, when a new serum drug level proved to be undetectable.Lessons:Our case suggests that the use of infliximab is safe in pregnancy, and drug discontinuation could be considered from the 24th week of pregnancy onward to reduce placental transfer to the newborn in patients at low risk of relapse. Vaccines with live attenuated organisms should be delayed for at least 6months or until the serum level of the medication is undetectable.
Keywords: biological therapy; case report; inflammatory bowel disease; pregnancy; ulcerative colitis